The Implementation of Islamic Religious Education Teachers’ Communication in Instilling Values of Honesty and Responsibility among Seventh-Grade Students: A Phenomenological Study - Wakib Kurniawan; Agung Nugroho Sulistyo (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
Islamic Religious Education (Pendidikan Agama Islam/PAI) is not merely concerned with the transmission of knowledge but with the transformation of values aimed at shaping moral character. Amid the currents of digitalization and social change, madrasahs are increasingly confronted with academic dishonesty and a weakening sense of responsibility, rendering teacher communication a strategic medium for the internalization of values within students’ everyday experiences. This study seeks to describe the forms and strategies of PAI teachers’ communication in cultivating honesty and responsibility, as well as to explore the meanings attributed by both teachers and students to this process. Employing a qualitative methodology with a phenomenological approach, the research was conducted at MTs Al-Ausath Karanganyar. Participants consisted of 2–3 PAI teachers and 5–6 seventh-grade students selected through purposive sampling. Data were collected through in-depth interviews, passive participant observation, and documentation studies, and were analyzed using the Miles and Huberman interactive model, supported by source triangulation and member checking. The thematic findings reveal four central axes of value-oriented communication: consistent role modeling, dialogical and contextualized advice, habituation accompanied by rational justification, and feedback that restores and sustains relational bonds. This study positions communicative experience as the primary analytical lens, shifting the focus from a mere inventory of techniques toward a shared meaning-making process through which values are enacted, experienced, and negotiated by teachers and students in the classroom.